CLITORIA TERNATEA — SOURCE OF FUNCTIONAL COMPONENT FOR ENRICHING YOGHURTS - KRYZHAK, LILIIA (Herald of Khmelnytskyi National University. Technical sciences, 2022)
In the dairy industry, the use of plant raw materials in the form of extracts, syrups, powders are considered in a promising area, as they contain a large number of biologically active substances.At the same time, yogurts are in great demand among various segments of the population, resulting in research aimed at developing the most popular fermented milk product with vegetable raw materials.The article theoretically substantiates and experimentally confirms the use of syrup and powder from Clitoria ternatea L. as a source of functional component in yogurts. The article proves the possibility of successful use of extract (syrup) and Clitoria ternatea powder in fermented dairy products.The technology of production and organoleptic parameters of yogurt with the use of syrup from the extract of dried flowers Clitoria ternatea - Butterfly pea flower tea Anchan is suggested. In order to improve the taste, 5 % syrup was added to the yogurt, and 0-4 % Anchan Matcha Genuine Tea powder was added to regulate the color intensity. Yogurt recipe with a mass fraction of 1,5 % fat has been developed; 2,5 % and 3,5 % with syrup and powder of clitoral triplet. Innovative thing is the fact that the yogurt production technology uses a fermentation composition of direct application «PRODALACT TSY BIO6» made in France, which differs from the traditional and contains a supplemented composition of crops: Lactobacillus delbrueckii ssp.bulgaricus, Streptococcus thermophilus, Lactobacillus acidus. Lactis.On the basis of the conducted researches, it is noted that anthocyanins of clitoris triple in the acidic environment change color, at change of pH in the alkaline part gives blue or violet color, therefore is perspective blue food dye.
Keywords: fermentation composition; yogurt; triple clitoris; extract; syrup; powder